2008
DOI: 10.1007/s00417-008-0881-9
|View full text |Cite
|
Sign up to set email alerts
|

German register for glaucoma patients with dry eye. I. Basic outcome with respect to dry eye

Abstract: We publish the first results from the German Glaucoma and Dry Eye Register. We found that the occurrence of dry eye is linked to several factors. Thus, the type of glaucoma has an impact on the risk of dry eye. The quantity of eye drops applied also plays a role in the development of the dry eye syndrome if more than three medications are used. While POAG is usually treated with one drug, PEX and PDG tend to be treated with multiple drugs. The gender difference in the occurrence of dry eye becomes apparent fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
97
3
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 32 publications
10
97
3
14
Order By: Relevance
“…Previous studies are showing a strong correlation between the number of IOP-lowering medications used and the presence of dry eye [8,16,17]. Study by Rossi et al [16] described the prevalence of OSD and they wanted to assess quality of life in subjects with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies are showing a strong correlation between the number of IOP-lowering medications used and the presence of dry eye [8,16,17]. Study by Rossi et al [16] described the prevalence of OSD and they wanted to assess quality of life in subjects with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were grouped into 4 categories by OSDI score: normal (scores 0-12), mild OSD symptoms (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate OSD symptoms (23-32), severe OSD symptoms (33-100) [13]. Patients' medical records were used to obtain medical history including detailed data on the use of medication and duration of therapy.…”
Section: Clinical and Experimental Ophthalmologymentioning
confidence: 99%
“…10 The German registry data found that women with glaucoma were significantly more likely to develop dry eye than men with glaucoma (56.9% versus 45.7%; p<0.0001). This is in agreement with other studies that found a predominance of DED in women, 5,6,8,11 but it seems to be an ethnic phenomenon because in Turkish normal volunteers 12 no significant differences in tear function between the genders have been observed, and in an Asian population the prevalence of DED was significantly higher in men compared with women.…”
Section: Gender and Age Differencesmentioning
confidence: 97%
“…This information has allowed the relationship between the occurrence of dry eye and potential causative factors to be dissected in detail. 10 Overall, 52.6% of glaucoma patients have a concomitant diagnosis of dry eye versus 47.4% who do not.…”
mentioning
confidence: 99%
“…Various observational studies conducted in recent years in Europe and the US have shown a consistent prevalence of OSD in glaucoma of approximately 50 % (range: 40 %-60 %) [1][2][3][4][5] with 27 % of patients suffering from severe OSD (see Figure 1). …”
mentioning
confidence: 91%